1997
DOI: 10.1074/jbc.272.49.30969
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Endothelial Vascular Cell Adhesion Molecule-1 Expression by Nitric Oxide Involves the Induction and Nuclear Translocation of IκBα

Abstract: The adhesion of circulating leukocytes to the vessel wall is an initiating event in atherogenesis and vascular inflammation (1, 2). Under certain conditions, the "activated" endothelium expresses cell surface adhesion molecules which mediate specific interactions between the endothelium and circulating leukocytes (3, 4). Factors that affect the induction of endothelial cell adhesion molecules such as vascular cell adhesion molecule (VCAM-1) 1 therefore may be important in regulating vascular inflammatory proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
133
2
2

Year Published

1998
1998
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 244 publications
(144 citation statements)
references
References 29 publications
(42 reference statements)
7
133
2
2
Order By: Relevance
“…17 The same group has subsequently reported that GSNO did not prevent phosphorylation and degradation of I B-␣ 15 minutes after stimulation with TNF-␣ in the same cells, suggesting that NO inhibits NF-B activation by the late (2 hours) induction and nuclear translocation of I B-␣. 28 In the present study, however, NOR3 itself had no effect on basal I B-␣ expression during a 75-minute incubation period. The exact reasons for the apparent discrepancy between their reports and ours are unknown.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…17 The same group has subsequently reported that GSNO did not prevent phosphorylation and degradation of I B-␣ 15 minutes after stimulation with TNF-␣ in the same cells, suggesting that NO inhibits NF-B activation by the late (2 hours) induction and nuclear translocation of I B-␣. 28 In the present study, however, NOR3 itself had no effect on basal I B-␣ expression during a 75-minute incubation period. The exact reasons for the apparent discrepancy between their reports and ours are unknown.…”
Section: Discussioncontrasting
confidence: 46%
“…26,27 However, our results appear to be in contrast to 2 recent (though contradictory) reports from the same laboratory. 17,28 Liao and his associates have shown that NO donors inhibited TNF-␣-induced NF-B activation by induction and stabilization of I B-␣ in human endothelial cells; S-nitrosoglutathione (GSNO) prevented I B-␣ degradation 30 minutes after stimulation with TNF-␣. 17 The same group has subsequently reported that GSNO did not prevent phosphorylation and degradation of I B-␣ 15 minutes after stimulation with TNF-␣ in the same cells, suggesting that NO inhibits NF-B activation by the late (2 hours) induction and nuclear translocation of I B-␣.…”
Section: Discussionmentioning
confidence: 99%
“…We showed that induction of NOS2 by LPS suppressed the secretion of pulmonary Th2 cytokines while others have shown that inhibition of NO exacerbates airway hyperresponsiveness, eosinophilia, and C-C chemokines (21). 2) NO may inhibit the expression of cell adhesion molecules (VCAM-1) on endothelial cells that are mediated, in part, by inhibition of kB cis-acting elements) (45), which in turn might block the influx of inflammatory T cells and eosinophils to the lung. 3) NO may trigger intrapulmonary cell death.…”
Section: Discussionmentioning
confidence: 99%
“…b-actin levels were used as a loading control (*P < 0.05, n ¼ 3). suppressing the inflammatory response induced by cytokines [48], inhibiting apoptosis [49], regulating cell migration, and angiogenesis [50,51]. Thus a stimulated increase in NO production by the EC in vitro could be a potential benefit, if such cells were used in lining a vascular graft.…”
Section: Discussionmentioning
confidence: 99%